PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN TINGKAT PENDIDIKAN TERHADAP KINERJA KARYAWAN DIVISI RETAIL BUSINESS DEVELOPMENT PT OK BANK INDONESIA - Hursepuny, Johan; Novita, Dwi; Wibowo, Kuncoro; Siagian, Frisca L; Marpaung, Oktavia L (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Human resources are a very important asset of a company. The quality of human resources will affect the progress of the company. For this reason, the quality of human resources in the company must always be improved so that their performance is satisfactory and will help the company make a profit. Many factors affect employee performance including work motivation, work discipline, education level. This study aims to determine the effect of work discipline, work motivation, level of education on the performance of employees of the retail business development division of PT OK Bank Indonesia, either partially or simultaneously. The sample of this study were 125 employees of the retail business development division of PT OK Bank Indonesia. The results showed that partially work discipline, work motivation, education level had a positive and significant effect on the performance of employees of the retail business development division of PT OK Bank Indonesia. Simultaneously work discipline, work motivation, education level also have a positive and significant effect on the performance of employees of the retail business development division of PT OK Bank Indonesia. The contribution of work discipline variables, work motivation, education level in influencing the employee performance variables of PT OK Bank Indonesia Retail Business Development division is 55.8%.